2008
DOI: 10.1053/j.gastro.2008.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Inactivation of Key Mitochondrial Proteins Leads to Dysfunction and Injury in Hepatic Ischemia Reperfusion

Abstract: SummaryBackground & Aims-Ischemia-reperfusion (I/R) is a major mechanism of liver injury following hepatic surgery or transplantation. Despite numerous reports on the role of oxidative/nitrosative stress and mitochondrial dysfunction in hepatic I/R injury, the proteins that are oxidatively-modified during I/R damage are poorly characterized. This study was aimed at investigating the oxidatively-modified proteins underlying the mechanism for mitochondrial dysfunction in hepatic I/R injury. We also studied the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
169
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(183 citation statements)
references
References 50 publications
11
169
0
1
Order By: Relevance
“…Indeed, several mitochondrial proteins, such as aldehyde dehydrogenase, are known to contain free sulfhydryl groups within their catalytic sites and are inactivated through S-nitrosylation (Moon et al, 2007;Andringa et al, 2008). Using an ischemia-reperfusion liver model, it was reported that ATP synthesis was markedly inhibited with the Snitrosylation of mitochondrial proteins such as 3-ketoacylCoA thiolase, and that pretreatment with a peroxynitrite scavenger restored enzyme activity and ATP synthesis (Moon et al, 2008). In addition, several key components of the mitochondrial respiration chain have altered function after their glutathionylation status has been changed (Beer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several mitochondrial proteins, such as aldehyde dehydrogenase, are known to contain free sulfhydryl groups within their catalytic sites and are inactivated through S-nitrosylation (Moon et al, 2007;Andringa et al, 2008). Using an ischemia-reperfusion liver model, it was reported that ATP synthesis was markedly inhibited with the Snitrosylation of mitochondrial proteins such as 3-ketoacylCoA thiolase, and that pretreatment with a peroxynitrite scavenger restored enzyme activity and ATP synthesis (Moon et al, 2008). In addition, several key components of the mitochondrial respiration chain have altered function after their glutathionylation status has been changed (Beer et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Because ALDH2 functions as an antioxidant enzyme, this protein may be easily inactivated by free radicals. Recently, ALDH2 was identified as a target for oxidative modification during glyceryl trinitrate tolerance (19,21) and hepatic ischemia-reperfusion (36). Therefore, oxidative modification of the thiol group may be responsible for ALDH2 inactivation under hyperglycemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo studies with the shorter methyl analogue, MnTM-4-PyP 5þ , were reported, presumably because of its commercial availability (191,223,224). With longer alkyl chains, bulkiness restrain toxic interactions with nucleic acids, whereas lipophilicity may compensate for the lower SOD-like activity.…”
Section: E Bioavailability Of Mn Porphyrinsmentioning
confidence: 99%